The novel HLA‐DQB1*03:493 allele, the first with glutamic acid at position—10 in the leader peptide. (30th August 2022) - Niño Ramírez, Jairo Eduardo; Gil Etayo, Francisco Javier; Vicente Parra, Ariadna; García Sanz, Ramón; Tejeda Velarde, Amalia
Abstract : A nonsynonymous nucleotide substitution in exon 1 results in the novel HLA‐DQB1*03:493 allele.